Anaphylaxis, Intra-Abdominal Infections, Skin Lacerations, and Behavioral Emergencies: A Literature Review of Austere Analogs for a near Earth Asteroid Mission - Menon, Anil S.; Watkins, Sharmi; Chough, Natacha G. (2012)
As space exploration is directed towards destinations beyond low-Earth orbit, the consequent new set of medical risks will drive requirements for new capabilities and more resources to ensure crew health. The Space Medicine Exploration Medical Conditions List (SMEMCL), developed by the Exploration Medical Capability element of the Human Research Program, addresses the risk of "unacceptable health and mission outcomes due to limitations of in-flight medical capabilities". It itemizes 85 evidence-based clinical requirements for eight different mission profiles and identifies conditions warranting further research and technology development. Each condition is given a clinical priority for each mission profile. Four conditions -- intra-abdominal infections, skin lacerations, anaphylaxis, and behavioral emergencies -- were selected as a starting point for analysis. A systematic literature review was performed to understand how these conditions are treated in austere, limited-resource, space-analog environments (i.e., high-altitude and mountain environments, submarines, military deployments, Antarctica, isolated wilderness environments, in-flight environments, and remote, resource-poor, rural environments). These environments serve as analogs to spaceflight because of their shared characteristics (limited medical resources, delay in communication, confined living quarters, difficulty with resupply, variable time to evacuation). Treatment of these four medical conditions in austere environments provides insight into medical equipment and training requirements for exploration-class missions.